AB0321 Negative correlation of the absolute number of cd4 +cd25+foxp3+regulatory t cells to the levels of rheumatoid factor in peripheral blood of new onset patients with rheumatoid arthritis. (12th June 2018) - Jianfang, X.; Gao, C.; Li, X.; Liu, G.
Abstract : Background: Rheumatoid arthritis (RA) is a progressive immune-mediated disease that can culminate in joint destruction and early mortality. High levels of serum RF are associated with a worse prognosis in RA. The role of is not fully understood. Recently, Our studies have found that the absolute number of peripheral CD4 + CD25 + Foxp3 + regulatory T (CD4 + Treg) cells decreased in RA patients. Interestingly, regulatory T cell epitopes (Tregitopes) in IgG have been reported as the main component of intravenous immunoglobulin therapy (IVIG) and provide one explanation for the expansion and activation of Treg cells following IVIg treatment. We hypothesise that RF joins with IgG to form large molecular complexes, which interrupts the production of Tregitopes in antigen presenting cells as a cause of reduction of CD4 + Treg cells. Objectives: The aim of this study is to investigate whether the absolute number of CD4 + Treg cells is associated with the titers of auto-antibodies in blood of new-onset diagnosed patients with RA. Methods: A total of 57 new-onset diagnosed patients with RA were enrolled and healthy donors as control. The absolute number of peripheral CD4 + Tregs cells was detected by multicolor flow cytometry combined with an internal microsphere counting standard. 46 of new-onset cases were tested the levels of RF and anti-CCP with ELISA method. IIF method was used to detect APF and AKA. Low titers group and high titers group around with the value 1:80. All data was analysed by SPSS 22.0. Results: The absolute number of CD4 + Treg cells in peripheral blood of new-onset patients with RA was significantly lower than in healthy controls [25.1 (16.01, 40.75) vs 33.0567 (22.9, 43.18), p<0.05]. Interestingly, the reduction of peripheral CD4 + Treg cells was negatively correlated to RF titers (correlation coefficient −0.488, p<0.01) but not to other auto-antibodies against CCP, APF and AKA. The absolute number of CD4 + Tregs in high titers RF group was lower than in low titers RF group [20.5 (14.0, 40.0 vs 34.0 (29.7, 44.6), p<0.05]. There was statistically significant difference in two titers groups. Conclusions: The absolute number of CD4 + Treg cells in peripheral blood of new-onset patients with RA was significantly decreased compared with that in health controls. Furthermore, the reduction of peripheral CD4 + Treg cells was negatively correlated to the titers of RF, suggesting that RF contributes to the reduction of CD4 +Tregs cells. The correlation of decreased CD4 + Treg and RF may be involved in the pathogenesis of poor prognosis in RA. Reference: [1] Cousens LP, Najafian N, Mingozzi F, Elyaman W, Mazer B, Moise L, Messitt TJ, Su Y, Sayegh M, High K, Khoury SJ, Scott DW, De Groot AS. In vitro and in vivo studies of IgG-derived Treg epitopes (Tregitopes): a promising new tool for tolerance induction and treatment of autoimmunity. J Clin Immunol2013Jan;33(Suppl 1):S43–9. doi:10.1007/s10875-012-9762-4 [Epub 2012 Sep 2. Review]. Disclosure of Interest: None declared